PENGARUH KESADARAN HALAL, INFLUENCER, DAN ASAL PRODUK TERHADAP MINAT BELI PRODUK SKINCARE SAFI DI KOTA PADANG - Mustion, Seppi; Nofriani, Olda; Wulandari, Natasya Amelia (Universitas Muhammadiyah Gresik, 2024)
The aim of the research is to analyze the influence of halal awareness, influencers and product origin on interest in using Safi skincare products in Padang City. In line with that, we also want to see how the relationship between age factors such as age and length of product use impacts interest in buying skincare, both directly and indirectly. An explanation of these factors will strengthen previous findings which state that the main factor is interest in purchasing halal skincare. The method used is quantitative research. This research uses g-form to distribute an online survey collecting primary data from a total of 112 data using SPSS 25 analysis tools. The results of this research are that the influence of halal product awareness has a positive effect on interest in buying halal safi products in the city of Padang and The influence of influencers has a positive effect on interest in buying Safi products in Padang City and the influence of product origin has no effect on interest in buying Safi products in Padang City. This has implications. Many consumers are still not aware that this continues to happen regarding the importance of halal awareness, even though halal is a crucial factor for the continuity of economic activities, including halal skin care products which are more guaranteed and in line with Islamic teachings. And Safi needs to increase halal awareness from the combination of the two strategically so that it can attract and increase consumer interest.